Evaluation of the Effects of Drying Methods on Post Aflatoxin Infection in Maize - Erastus Dushimeyesu; Sylvestre Habimana; Fabrice Musana Rwalinda (Turkish Journal of Agriculture: Food Science and Technology)
The cultivation and the usage of maize have been significantly increased across all provinces of Rwanda. Nevertheless, the problem of aflatoxin contamination remains a major factor that renders them to be unfit for animal and human consumption. In this research, the effects of drying methods (sun drying, kitchen drying, dry shelter) post aflatoxin infection in maize were evaluated in Northern Rwanda. A randomized complete block design with four replications was used with maize variety (H628) with drying methods as the main plot. Maize samples were tested for aflatoxin using aflatest. In both seasons (2021 A and 2021 B) the aflatoxin results show that the aflatoxin infection levels were lower in maize dried with kitchen drying (1.4 ppb) compared to the samples dried with sun drying (1.6 ppb) and dry shelter (2.2). Also, it was seen that the three drying methods are good for reducing the aflatoxin infection levels lower than 10 ppb as standards limit for East African countries. The aflatoxin infection levels were found to be significant (≤10 ppb) as results of kitchen drying than sun drying and dry shelter methods. This research resulted that proper drying such as drying maize on kitchen fire (kitchen drying) produce the lower level of aflatoxin infection in maize.